Teaching Learning Pattern of Children in the Flood Area - Hartini, Nurul (Faculty of Psychology, Universitas Surabaya, 2010)
How does the teaching learning pattern of children in a flood area? Utilising interview, observation and focus group discussions, a study was conducted to 30 kindergarten and elementary school teachers in a flood zone in Bojonegoro region, including Dander, Trucuk, Kalitidu, Kanor, and Bau- reno. Results indicate that the community, particularly children have seen floods as a regular phe- nomenon and thus has made peace with this experience. Children motivation for going to school and learning remain intact and high in all conditions including when the flood came. The level of children's motivation for school and learning are positive potentials that should be maintained. Co- operation between the government, schools, and community are needed in order to accelerate the normalization process, particularly in developing an optimal situation for the children to learn and go to school during a flood and right after, as well. Bagaimana gambaran pola pembelajaran anak-anak di daerah banjir? Hasil studi lapangan melalui interview, observasi dan diskusi terfokus yang dilakukan kepada 30 orang guru Taman Kanak- Kanak dan Sekolah Dasar di daerah rawan banjir Kecamatan Dander, Trucuk, Kalitidu, Kanor, dan Baureno, Bojonegoro menunjukkan bahwa masyarakat dan anak-anak Bojonegoro sudah ”berdamai” dengan bencana banjir. Motivasi bersekolah dan motivasi belajar anak-anak tetap besar dalam semua kondisi termasuk ketika banjir. Besarnya motivasi anak-anak untuk bersekolah dan belajar merupakan potensi positif yang harus dipertahankan. Untuk itu, perlu kerjasama antara pemerintah, sekolah, dan masyarakat untuk segera mengembalikan anak-anak pada situasi normal untuk bersekolah dan belajar ketika terjadi dan pasca-banjir.